The Reducing Agent Dithiothreitol Modulates the Ventilatory Responses That Occur in Freely Moving Rats during and following a Hypoxic-Hypercapnic Challenge - Paulina M. Getsy; Gregory A. Coffee; Walter J. May; Santhosh M. Baby; James N. Bates; Stephen J. Lewis (MDPI AG, 2024)
The present study examined the hypothesis that changes in the oxidation-reduction state of thiol residues in functional proteins play a major role in the expression of the ventilatory responses in conscious rats that occur during a hypoxic-hypercapnic (HH) gas challenge and upon return to room air. A HH gas challenge in vehicle-treated rats elicited robust and sustained increases in minute volume (via increases in frequency of breathing and tidal volume), peak inspiratory and expiratory flows, and inspiratory and expiratory drives while minimally affecting the non-eupneic breathing index (NEBI). The HH-induced increases in these parameters, except for frequency of breathing, were substantially diminished in rats pre-treated with the potent and lipophilic disulfide-reducing agent, L,D-dithiothreitol (100 µmol/kg, IV). The ventilatory responses that occurred upon return to room air were also substantially different in dithiothreitol-treated rats. In contrast, pre-treatment with a substantially higher dose (500 µmol/kg, IV) of the lipophilic congener of the monosulfide, N-acetyl-L-cysteine methyl ester (L-NACme), only minimally affected the expression of the above-mentioned ventilatory responses that occurred during the HH gas challenge or upon return to room air. The effectiveness of dithiothreitol suggests that the oxidation of thiol residues occurs during exposure to a HH gas challenge and that this process plays an essential role in allowing for the expression of the post-HH excitatory phase in breathing. However, this interpretation is contradicted by the lack of effects of L-NACme. This apparent conundrum may be explained by the disulfide structure affording unique functional properties to dithiothreitol in comparison to monosulfides. More specifically, the disulfide structure may give dithiothreitol the ability to alter the conformational state of functional proteins while transferring electrons. It is also possible that dithiothreitol is simply a more efficient reducing agent following systemic injection, although one interpretation of the data is that the effects of dithiothreitol are not due to its reducing ability.